Cardiodynamic state is associated with systemic inflammation and fatal acute‐on‐chronic liver failure. (30th March 2020) - Praktiknjo, Michael; Monteiro, Sofia; Grandt, Josephine; Kimer, Nina; Madsen, Jan L.; Werge, Mikkel P.; William, Peter; Brol, Maximilian J.; Turco, Laura; Schierwagen, Robert; Chang, Johannes; Klein, Sabine; et al.
Abstract: Background & Aims: Acute‐on‐chronic liver failure (ACLF) is characterized by high short‐term mortality and systemic inflammation (SI). Recently, different cardiodynamic states were shown to independently predict outcomes in cirrhosis. The relationship between cardiodynamic states, SI, and portal hypertension and their impact on ACLF development remains unclear. The aim of this study was therefore to evaluate the interplay of cardiodynamic state and SI on fatal ACLF development in cirrhosis. Results: At inclusion, hemodynamic measures including cardiac index (CI) and hepatic venous pressure gradient of 208 patients were measured. Patients were followed prospectively for fatal ACLF development (primary endpoint). SI was assessed by proinflammatory markers such as interleukins (ILs) 6 and 8 and soluble IL‐33 receptor (sIL‐33R). Patients were divided according to CI (<3.2; 3.2‐4.2; >4.2 L/min/m 2 ) in hypo‐ (n = 84), normo‐ (n = 69) and hyperdynamic group (n = 55). After a median follow‐up of 3 years, the highest risk of fatal ACLF was seen in hyperdynamic (35%) and hypodynamic patients (25%) compared with normodynamic (14%) ( P  = .011). Hyperdynamic patients showed the highest rate of SI. The detectable level of IL‐6 was an independent predictor of fatal ACLF development. Conclusions: Cirrhotic patients with hyperdynamic and hypodynamic circulation have a higher risk of fatal ACLF. Therefore, the cardiodynamic state is strongly associated with SI, which is an independent predictor of development of fatal ACLF.